Buccal cells submitted to three different storage conditions before DNA extraction - Fernanda Nedel; Dárvi de Almeida André; Isabel Oliveira de Oliveira; Sandra Beatriz Chaves Tarquinio; Flávio Fernando Demarco (University of São Paulo, 2009)
This study evaluated quantitatively and qualitatively the effect of the storage time of samples before the application of the cell lysis solution (CLS) for extracting DNA from buccal cells (BC). BC from the upper and lower gutter region were collected from 5 volunteers using special cytobrushes (Gentra), totaling 3 collections for each individual. In the control group (n=10), CLS was applied soon after BC collection. In the other two groups, samples were stored at room temperature (n=10) or at 4°C (n=10). After CLS application, DNA was extracted according to the manufacturer's instructions (Puregene DNA Buccal Cell Kit; Gentra Systems, Inc.). The DNA obtained was evaluated by two calibrated blind examiners using spectrophotometry and analysis of DNA bands (0.8% agarose gel electrophoresis). The obtained data were submitted to one-way ANOVA. The means and standard deviations for DNA extracted under immediate, room temperature and cooling temperature conditions were 3.5 ± 0.7, 3.0 ± 0.6 and 4.1 ± 1.8 µg, respectively (p=0.385). No significant differences were found in relation to the amount of DNA for the different storage conditions. However, in the visual analysis of the DNA bands, no trace of DNA degradation was detected when CSL was applied soon after DNA collection, while DNA bands with degradation could be observed in the other groups. Within the limitations of the study, it may be concluded that CLS should be applied soon after DNA collection in order to obtain high-quality DNA from BC.